2015
DOI: 10.1021/ml500409n
|View full text |Cite
|
Sign up to set email alerts
|

MLN8054 and Alisertib (MLN8237): Discovery of Selective Oral Aurora A Inhibitors

Abstract: The Aurora kinases are essential for cell mitosis, and the dysregulation of Aurora A and B have been linked to the etiology of human cancers. Investigational agents MLN8054 (8) and alisertib (MLN8237, 10) have been identified as high affinity, selective, orally bioavailable inhibitors of Aurora A that have advanced into human clinical trials. Alisertib (10) is currently being evaluated in multiple Phase II and III clinical trials in hematological malignancies and solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 17 publications
3
51
0
Order By: Relevance
“…Interestingly, MLN8054 contains a benzodiazepine core scaffold; however, a small structural change in the periphery of the molecule abrogated GABA A α-1 benzodiazepine binding and clinical incidence of somnolence in the follow-on candidate alisertib MLN8237 (Figure 5D), further emphasizing the subtlety of fine-tuning specific ligand-protein interactions (Sells et al., 2015). …”
Section: Main Textmentioning
confidence: 98%
“…Interestingly, MLN8054 contains a benzodiazepine core scaffold; however, a small structural change in the periphery of the molecule abrogated GABA A α-1 benzodiazepine binding and clinical incidence of somnolence in the follow-on candidate alisertib MLN8237 (Figure 5D), further emphasizing the subtlety of fine-tuning specific ligand-protein interactions (Sells et al., 2015). …”
Section: Main Textmentioning
confidence: 98%
“…Alisertib (MLN8237) inhibits Aurora-A and Aurora-B kinase with an IC50 of 1.2 nM and 396.5 nM, respectively (39,40). Alisertib displays activity in preclinical models of lung, prostate, ovarian, and lymphoma cells (41).…”
Section: Aurora Kinase Inhibitionmentioning
confidence: 99%
“…The Aurora-A kinase inhibitor Alisertib is currently being tested in phases II and III clinical trials [47]. A comprehensive phase II clinical trial recently showed promising results in treatments for advanced lung and breast cancer [48].…”
Section: Discussionmentioning
confidence: 99%